A DFT Analysis on Antioxidant and Antiradical Activities from Anthraquinones Isolated from the Cameroonian Flora. (24th June 2019) - Ngo Nyobe, Judith Caroline; Eyia Andiga, Laurent Gael; Mama, Désiré Bikele; Ateba Amana, Baruch; Zobo Mfomo, Joseph; Flavien Aristide Alfred, Toze; Ndom, Jean Claude
Abstract : The present work is devoted to the exploration antioxidant and antiradical activity of twenty anthraquinones isolated from the Cameroonian flora at B3LYP/6-311++G(d, p) level of theory using the B3LYP/6-31 + G(d, p) geometrical data as geometry optimization starting points. The single electron transfer mechanism has been adopted to examine both biological activities. The classification of the antiradical profile to integrate the electrodonating power (ω − ), electroaccepting power (ω + ), donor index ( R d ) and acceptor index ( R a ) has been performed using the donor-acceptor map (DAM). The antioxidant and radical powers of compounds analyzed have been compared to that of two classical vitamins (vitamin C and gallic acid). The stability of each anthraquinone derivative of the molecular library has been developed according to thermodynamic and kinetic concepts. The global reactivity descriptors (GRDs; electrophilicity index ( ω ), electronegativity ( χ ), global softness (S), and global hardness ( η )) have been used to analyze the reactivity. The topological analysis of optimized structures indicates that the strength of the hydrogen bonds formed is situated between 44.205 and 52.001 kJ/mol. Our B3LYP results reveal that 3-methoxy-1-vismiaquinone (in a configuration without hydrogen bond) exhibits the best antioxidant capacity in gas phase. A comparison between antioxidant performance of molecules examined and that of classical vitamins (gallic acid, caffeic acid, ferulic acid, and ascorbic acid (vitamin C)) displayed the fact that the single electron transfer (SET) mechanism is more prominent for compounds of the molecular library analyzed. In the same vein, the antiradical behaviors of anthraquinone derivatives have shown to be higher than that of gallic acid and vitamin C in gas phase and water. The 5, 8-dihydroxy-2-methylantraquinone structure in a configuration bearing one hydrogen bond has been found to be the best antiradical of the series in aqueous solution.